Mocaf flour as an alternative ingredient: A study on batik-patterned cookies - Nur Wahyuni, Nur Wahyuni; Ab. Latif, Zahidah (UUMPRESS and Managed by STML, 2020)
The mocaf flour also known as modified cassava flour is flour that is modified by using microbial fermentation techniques. It has similar physical and chemical characteristics that could substitute wheat flour. This study aims to obtain the composition or formula in making batik – patterned cookies as well as attaining public acceptance of the product. A series of four combinations of mocaf and wheat flour were formulated and an acceptance test was carried out on 30 panelists in Yogyakarta within August and October 2019. The findings disclosed that the cookie sample X3 with the combination of 150 gram mocaf flour and 50 gram wheat flour had the highest value (M = color: 3.37; aroma: 3.13; texture: 3.20; and taste: 3.33). This study is the first to assess the acceptance rate of batik – patterned cookies using mocaf flour. The significant results deepen our understandings of the demand of the consumers in order to increase selling value thus indirectly promoting the batik motifs to the consumers.